Profile of Chief Medical Officers and performance of health zones in crisis contexts: a cross-sectional study in three provinces of the Eastern Democratic Republic of Congo - Rosine Bigirinama; Jean-Corneille Lembebu; Christian Chiribagula; Pacifique Mwene-Batu; Denis Porignon; Abdon Mukalay; Albert Mwembo; Ghislain Bisimwa (Human Resources for Health)
Abstract Context In crisis-affected health systems, the performance of health zones (also known as health districts) is challenged by recurrent armed conflicts and state fragility. The profiles of health zone managers and contextual factors can significantly influence the zones' ability to effectively respond to population health needs. This study explores these interactions to identify key factors associated with health zones performances in three provinces of Eastern Democratic Republic of Congo (DRC), a region that has endured over three decades of conflict. Methods This mixed-methods study was conducted between October 2022 and April 2024, using data covering the period from 2017 to 2022. In the DRC, health zones are managed by Chief Medical Officers (CMOs). We assessed the functionality and performance of health zones using key indicators related to primary healthcare delivery and management. Data on CMO profiles and the operational contexts of their health zones were analyzed to identify factors influencing functionality and performance, through multivariate regressions (p < 0.05). In addition, 17 individual interviews with key health system actors were analyzed thematically to capture perceptions on CMO performance and stability. Results CMOs with training in primary healthcare management and extensive professional experience were statistically associated with higher health zone performance. Conversely, instability among CMOs, due to frequent rotations driven by political influences and weak collaboration between decision-making bodies, negatively impacted performance. However, support from international and faith-based partners was associated with improved health zone performance. Conclusions This study highlights the importance of investing in capacity-building for health managers to strengthen health systems and improve resilience in crisis settings. Establishing robust governance frameworks that promotes transparency in the recruitment and management of health managers, and ensure stability in human resources, is critical for maintaining and improving health system performance.